Total Factor Productivity Estimates: Some Evidence from European Regions - Maria Gabriela Ladu (Austrian Institute of Economic Research (WIFO), 2010)
This paper analyses the economic performance of European Regions and computes the Total Factor Productivity (TFP) using a panel cointegration approach. The main idea behind this choice is that this approach allows to directly estimate differences across economies in the production function and also to test for the presence of scale economies and market imperfections. In fact, recent studies (de la Fuente, 1995, 1996B, and de la Fuente - Doménech, 2000) show that TFP differences across countries and regions are substantial and highlight the importance of TFP dynamics as crucial in the evolution of productivity.
Keywords: 330; Total Factor Productivity; Panel Unit Root Test; Panel Cointegration; Fully Modified OLS; Produktivität; Panel; Einheitswurzeltest; Kointegration; Kleinste-Quadrate-Methode; Schätzung; Europa